The Coupling of Primary School Music Education and Local Cultural Inheritance under the New Curriculum Standard Perspective in China - Lu, Yixuan; Lu, Liwei (Journal of Educational Research and Policies, 2025)
To promote the well-rounded development of primary school students and further enhance their musical literacy, the Ministry of Education issued the Compulsory Education Arts Curriculum Standards (2022 Edition) (hereinafter referred to as the “New Curriculum Standards”). The overall objectives of the New Curriculum Standards introduce new requirements, including “enhancing aesthetic competence,” “improving artistic expression,” “boosting creative practical abilities,” “forging a strong sense of community for the Chinese nation,” and “understanding the historical and cultural traditions of different regions, ethnic groups, and countries.” The curriculum concepts and implementation suggestions of the New Curriculum Standards present new demands and pathways for music teaching. This research delves into the integrated development of primary school music education and local cultural inheritance in this area under the perspective of the New Curriculum Standards. Through analysis of relevant research, the study clarifies pertinent issues and proposes corresponding recommendations. The aim is to facilitate the inheritance and development of local culture and achieve the overall teaching objectives set forth by the New Curriculum Standards.